2016
DOI: 10.15761/jsin.1000147
|View full text |Cite
|
Sign up to set email alerts
|

Treating depression with exercise: The inflammasome inhibition perspective

Abstract: Patients with chronic inflammation present increased blood levels of circulating cytokines and often are associated with symptoms of depression. The activation of the immune cells microglia in the brain of depressed patients has been associated with a greater prevalence of suicide, indicating a crucial role of neuroinflammation in the neuropathology of depression. In the modern lifestyle, decreased physical activity and increased sedentarism have emerged as risk factors for mental disorders, including depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 105 publications
0
6
0
Order By: Relevance
“…Neopterin has been used as a sensitive clinical biomarker for immune system activation for over decades. Increased neopterin levels in biological fluids have been proposed by our group and others to be a biomarker of exhaustive or high intensity physical exercise-induced inflammation [39,40,135,[143][144][145][146]. Many reports have demonstrated that a sedentary lifestyle or reduced physical activity have increased levels of several markers of inflammation, such as C-reactive protein, IL-18, IL-6, TNF-α, that correlated with increased neopterin levels in the blood [64,145,147].…”
Section: Physical Exercise and Neopterinmentioning
confidence: 94%
See 2 more Smart Citations
“…Neopterin has been used as a sensitive clinical biomarker for immune system activation for over decades. Increased neopterin levels in biological fluids have been proposed by our group and others to be a biomarker of exhaustive or high intensity physical exercise-induced inflammation [39,40,135,[143][144][145][146]. Many reports have demonstrated that a sedentary lifestyle or reduced physical activity have increased levels of several markers of inflammation, such as C-reactive protein, IL-18, IL-6, TNF-α, that correlated with increased neopterin levels in the blood [64,145,147].…”
Section: Physical Exercise and Neopterinmentioning
confidence: 94%
“…Other CNS alterations has shown altered monoaminergic metabolism, like the down-regulation of the biosynthesis of serotonin, which is implicated in the physiopathology of depression [133]. In addition, increased blood levels of pro-inflammatory mediators, e.g., IL-8 and TNF-α, with low levels of BDNF have been documented in individuals affected by depression [134][135][136]. Exercise is considered a first-line treatment in mild to moderate depression [135,137,138].…”
Section: Physical Exercise As a Non-pharmacological Intervention For Neuroprotectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute inflammation can play a protective role by responding to cellular stress signals that result from immune cell activation and the injured tissue [ 37 , 38 ]. Low-level chronic inflammation is typified by the elevation of specific proinflammatory mediators that are associated with many chronic disorders and are important in the pathogenesis of diabetes and obesity, as well as other systemic disorders and even neurological diseases [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Schuch et al, in their review on acute and chronic biomarker responses to exercise, found no consistent association between inflammation, exercise, and depression [37], whereas other authors found an influence of physical exercise on the acquired immunity or the kynurenine pathway [20]. In summary, studies are abundant and detailed but not homogeneous [13,19,39,42,[46][47][48].…”
Section: Immunomodulatory Effects Of Exercise In the Treatment Of Depressionmentioning
confidence: 99%